Optimal Financial Contracting with ex post and ex ante Observability Problems - Campbell, T. S.; Chan, Y.-S. (Quarterly Journal of Economics, 1992)
Tim S. Campbell, Yuk-Shee Chan; Optimal Financial Contracting with ex post and ex ante Observability Problems*, The Quarterly Journal of Economics, Volume